Mo3S132− Intercalated Layered Double Hydroxide: Highly Selective Removal of Heavy Metals and Simultaneous Reduction of Ag+ Ions to Metallic Ag0 Ribbons. (23rd November 2021) - Yang, Lixiao; Xie, Linxia; Chu, Menglin; Wang, Hui; Yuan, Mengwei; Yu, Zihuan; Wang, Chaonan; Yao, Huiqin; Islam, Saiful M.; Shi, Keren; Yan, Dongpeng; Ma, Shulan; et al.
Abstract: We demonstrate a new material by intercalating Mo3 S13 2− into Mg/Al layered double hydroxide ( abbr . Mo3 S13 ‐LDH), exhibiting excellent capture capability for toxic Hg 2+ and noble metal silver (Ag). The as‐prepared Mo3 S13 ‐LDH displays ultra‐high selectivity of Ag +, Hg 2+ and Cu 2+ in the presence of various competitive ions, with the order of Ag + >Hg 2+ >Cu 2+ >Pb 2+ ≥Co 2+, Ni 2+, Zn 2+, Cd 2+ . For Ag + and Hg 2+, extremely fast adsorption rates (≈90 % within 10 min, >99 % in 1 h) are observed. Much high selectivity is present for Ag + and Cu 2+, especially for trace amounts of Ag + (≈1 ppm), achieving a large separation factor (SFAg/Cu ) of ≈8000 at the large Cu/Ag ratio of 520. The overwhelming adsorption capacities for Ag + ( q m Ag =1073 mg g −1 ) and Hg 2+ ( q m Hg =594 mg g −1 ) place the Mo3 S13 ‐LDH at the top of performing sorbent materials. Most importantly, Mo3 S13 ‐LDH captures Ag + via two paths: a) formation of Ag2 S due to Ag‐S complexation and precipitation, and b) reduction of Ag + to metallic silver (Ag 0 ). The Mo3 S13 ‐LDH is a promising material to extract low‐grade silver from copper‐rich minerals and trap highly toxic Hg 2+ from polluted water. Abstract : Intercalation of Mo3 S13 2− into MgAl‐layered double hydroxide (LDH) gives a new material, Mo3 S13 ‐LDH, which exhibits enormous adsorption capacities of noble metal silver ( q m Ag =1073 mg g −1 ) and toxic Hg 2+ ( q m Hg =594 mg g −1 ) as well as high uptake selectivity for Ag + and Cu 2+ . Both S2 2− and Mo 4+ in Mo3 S13 ‐LDH contribute to the reduction of Ag + to metallic Ag 0 .